Comparative characteristic of long-term results of transnannular and non-transanular repair of the right ventriculic outlet tract in patients with double outlet right ventricle tetralogy of fallo type - I. Dziuryi; Y. Truba; S. Boyko; V. Balabushka; M. Rudenko; V. Lazoryshynetz (Ukrainian Journal of Cardiovascular Surgery, 2018)
Double outlet right ventricle (DORV), ToF type is discordant ventriculoarterial connection at which both great arteries completely or particularly arise from the right ventricle, combined with stenosis of pulmonary artery. Method of treatment includes tunnel formation of correct construction between the left ventricle and aorta, and adequate right ventricle outflow tract obstruction repair (RVOTO). The main purpose of this work is to make the comparative characteristic of the late-results of surgical treatment of double outlet right ventricle, ToF type using the transannular and non-transannular techniques.Materials and methods. From January 2006 to December 2016 in “Amosov National Institute of Cardiovascular Surgery NAMS Ukraine”, consistently were operated 33 patients with double outlet right ventricle, ToF type. Depending on the method the pulmonary stenosis repair, patients was divided in two groups: first group 14 (43%) patients, which were performed RVOT transannular repair . Second group 19 (57%) patients, which were performed different kinds of non-transannular techniques.Results. Hospital mortality was 3% (n=1). Late-results was observed in 30 (90%) patients, term of observation was 50±21,8 (from 12 to 80) months. Arrhythmogenic complications during long-term period were noticed in 3 patients in the first group. In 14 patients after transannular repair the systolic pressure gradient (GSP) on the pulmonary valve was 19±6 mmHg (12– 28 mmHg), pulmonary valve insufficiency is moderate, while in late-period the pulmonary valve insufficiency was observed from moderate to mild 16±3,7 mmHg (12–23 mmHg). In 16 patients which was performed pulmonary valve-saved repair, systolic pressure gradient on the pulmonary valve after repair was 21±7 mmHg (15–30 mmHg), while in remote period was 19+6 mmHg (10–30 mmHg), and the pulmonary valve insufficiency is absent.Conclusions. The less-traumatic technique of RVOTO repair with saving the pulmonary valve, provides good early and long-term results of DORV (ToF type) repair, helps to save geometry RV and right ventricular contraction, and prevent complications in the long-term perspective. However the remote survival statistically is not different in comparison groups.